Conceptualization of depth of vocabulary knowledge with academic reading comprehension - Hasan, Md Kamrul; Shabdin, Ahmad Affendi (Chulalongkorn University Language Institute, 2016)
The present study embodies a conceptual framework, and it studies the concept regarding the depth of vocabulary knowledge. Literature review is employed as a foundation for developing the conceptual framework for the present study. The current study suggests that different dimensions of depth of vocabulary knowledge, namely paradigmatic relations, syntagmatic relations, analytic relations and morphological knowledge need to be included as integral parts of depth of vocabulary knowledge to examine their correlation and prediction on academic reading comprehension. In addition, different relationships of paradigmatic relations, syntagmatic relations, analytic relations and morphological knowledge with reading comprehension are explored.At last, the paper suggests a conceptual framework of depth of vocabulary knowledge and its relationship with academic reading comprehension, and future research works need to encompass paradigmatic relations, syntagmatic relations, analytic relations and morphological knowledge as integral parts of depth of vocabulary knowledge in relation with academic reading comprehension.